ECONOMİC ANALYSİS OF MEDİCAL ROBOTİCS: MANAGİNG FİNANCİAL RİSKS İN THE DEVELOPMENT AND DEPLOYMENT OF SURGİCAL TECHNOLOGİES - Arzu Jamil Safarli; Gulzar Jamil Safarli (Theoretical Hypotheses and Empirical Results, 2025)
Medical robotics is revolutionizing healthcare by improving surgical precision and patient outcomes. However, its development and deployment involve substantial financial risks. High research and production costs, regulatory hurdles, and uncertain market adoption present challenges for investors, healthcare providers, and policymakers. Effective financial risk management strategies are essential to mitigate these uncertainties. Diversified investment portfolios, strategic partnerships, and government incentives can help stabilize funding. Additionally, insurance models and value-based pricing can reduce financial burdens on hospitals. This paper examines the economic implications of medical robotics, highlighting risk management approaches that ensure sustainable growth. By addressing financial challenges, stakeholders can maximize the benefits of robotic technology while minimizing potential economic drawbacks in the evolving healthcare landscape.